Critical CALL – Proceedings of the 2015 EUROCALL Conference, Padova, Italy 2015
DOI: 10.14705/rpnet.2015.000339
|View full text |Cite
|
Sign up to set email alerts
|

The integration of a three-year-long intercultural collaborative project into a foreign language classroom for the development of intercultural competence

Abstract: Many studies on intercultural communication introduced how their collaborative projects were conducted. There are also several studies that discuss how intercultural collaborative activities can be integrated into a foreign language curriculum, as well as a big project (the INTENT project) that helps teachers integrate collaborative activities into their language curricula. Nonetheless, intercultural collaborative projects have not yet been mainstreamed for various reasons, such as insufficient pedagogical sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Studies on integrated curriculum with regard to intercultural competence or sensitivity developing (Ferguson-Patrick, Reynolds, and Macqueen, 2018; Hirotani and Fujii, 2015; Li, 2017; McRae and Ramji, 2017; Taraban-Gordon and Page, 2017) have been encountered recently in the literature. In a study by Hirotani and Fujii (2015), it was ascertained that the integration of the intercultural collaborative activities with the foreign language curriculum contributed to students' reflection of what they had learned about cultural differences and similarities. Ayvaz- Tuncel (2009) concluded that the communication, cooperation and social problem solving skills and the self-respect of the experimental group, which was administered an integrated curriculum developed more than the control group.…”
Section: Integrated Curriculum and Interculturalitymentioning
confidence: 99%
“…Studies on integrated curriculum with regard to intercultural competence or sensitivity developing (Ferguson-Patrick, Reynolds, and Macqueen, 2018; Hirotani and Fujii, 2015; Li, 2017; McRae and Ramji, 2017; Taraban-Gordon and Page, 2017) have been encountered recently in the literature. In a study by Hirotani and Fujii (2015), it was ascertained that the integration of the intercultural collaborative activities with the foreign language curriculum contributed to students' reflection of what they had learned about cultural differences and similarities. Ayvaz- Tuncel (2009) concluded that the communication, cooperation and social problem solving skills and the self-respect of the experimental group, which was administered an integrated curriculum developed more than the control group.…”
Section: Integrated Curriculum and Interculturalitymentioning
confidence: 99%